The results of patients with histopathological diagnosed xanthogranulomatous cholecystitis: A single-center experience - Avanaz, Ali; Aras, Ulas (Annals of Medical Research, 2024)
Aim: Xanthogranulomatous cholecystitis (XGC) is a rare and benign gallbladder disorder. Unnecessary or additional surgical interventions were reported secondary to extended inflammation or suspicion of malignancy. This study aimed to examine patients diagnosed with XGC in our clinic. Materials and Methods: The data of patients were recruited who underwent cholecystectomy and diagnosed with XGC. We excluded patients with no radiologic examination, accompanying pancreas, biliary tree, and hepatic cancer. We recruited the data of patients’ demographics, clinical symptoms, imaging studies, characteristics of surgery, and postoperative outcomes. Results: The mean age was 57 ±19.1 years, and there were 12 (31%) females. Abdominal pain was found in 38 (97%) patients as a significant complaint. Elective and emergent cholecystectomy were performed in 18 (46%) and 21 (54%) patients, respectively. Open surgery was performed on 17 (44%) patients, and laparoscopic surgery on 22 (56%). The surgery was completed as laparoscopic in 17 (77%) patients. According to radiologic examinations, suspicious gallbladder malignancy was reported in 4 (10%), 8 (20%), and 4 (10%) patients with USG, CT, and MRI, respectively. There was 1 (3%) patient diagnosed with XGC by USG, 4 (10%) by CT, and 1 (3%) by MRI. Common bile duct (CBD) stone was observed in 10 (26%) of 39 patients. Conversion to open surgery was found in 5 (13%) patients. Intraoperative frozen section analysis was performed in 8 (20%) patients. Extended surgery was performed to 7 (17%) patients. Conclusion: Preoperative diagnosis and surgical management of XGC can be challenging. If a surgeon has suspicion of XGC in preoperative period, expert radiologist opinion should be asked, and they should always keep in mind to perform frozen-section examination.